Tactile Detection in Fibromyalgia: A Systematic Review and a Meta-Analysis - Augière, Tania; Desjardins, Audrey; Paquette Raynard, Emmanuelle; Brun, Clémentine; Pinard, Anne Marie; Simoneau, Martin; Mercier, Catherine (Frontiers in Pain Research, 2021)
Fibromyalgia is a chronic pain syndrome characterized by sensorimotor deficits and distortions of body representation, that could both be caused by alterations in sensory processing. Several studies suggest a hypersensitivity to various sensory stimulations in fibromyalgia but results on detection of both noxious and non-noxious tactile stimulation, which are particularly relevant for body representation and motor control, remain conflicting. Therefore, the aim of this study is to systematically review and quantify the detection thresholds to noxious and non-noxious tactile stimuli in individuals with fibromyalgia compared to pain-free controls. A systematic review and a meta-analysis were performed in the MEDLINE, EMBASE, CINAHL, Cochrane, PsycInfo and Web of Science databases using keywords related to fibromyalgia, tactile pain threshold, tactile detection threshold and quantitative sensory testing. Nineteen studies were included in the review, with 12 in the meta-analysis. Despite the heterogeneity of the results, the data from both the review and from the meta-analysis suggest a trend towards hyperalgesia and no difference of sensitivity to non-noxious tactile stimuli in participants with fibromyalgia compared to healthy controls. This contradicts the hypothesis of a general increase in responsiveness of the central nervous system to noxious and non-noxious stimulations in fibromyalgia. This study shows no alteration of the sensitivity to non-noxious tactile stimulation in fibromyalgia, suggesting that an altered unimodal processing is not sufficient to explain symptoms such as sensorimotor impairments and body distortions. Future research should investigate whether alterations in multisensory integration could contribute to these symptoms.